Audit quality interpretation and one of the possible measurement models - Szirmai, Madarsiné Andrea; Siklósi, Ágnes; Török, Martina Zsófia (Research Papers of Wrocław University of Economics, 2018)
As a key issue, we deal with the relationship between audit quality and business. The economic crisis and the increased audit threshold have reduced the scope of firms obligated to audit. From the available data, it can be seen that although the number of firms fall under statutory audit decreased, the number of audit companies declined only marginally, resulting in a strong price competition, which led to the issue of audit quality coming to the fore. Based on the results of the systematic research carried out, an audit quality interpretation and measurement model can be established. The model examines the audit quality in five themes and three dimensions, which provides a full measure of quality. The five themes allow us to interpret six types of service quality gap. Using this model we can identify areas in need of improvement, helping to provide a more efficient and effective audit and, consequently, a higher customer satisfaction
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 166-173
Keywords: audit; quality measurement; audyt; jakość pomiaru